由“继善成性”到“成性存存” ：试论儒家哲学“善”概念 的两层含义 = From the “experiential stage” to the “transcendent stage” of moral existence : a commentary on the multiple connotations of the “Shan” concept in confucian tradition. - 侯展捷 How, Zhan Jie (2013)
“善”是儒家道德哲学中一个核心的概念，同时亦构成了孟子心性论的主轴。台湾大学的傅佩荣教授曾对“善”概念作出如下的定义：“人与人之间适当关系的实 现”。傅氏定义的长处在于最大程度的涵括了儒家的“仁”、“义”、“礼”、“智”、“孝”、“悌”等诸德目，而且在儒家原典中亦不乏相应的论述。但是，此 定义仅将儒家对主体的道德期许局限在一经验性的层次上，从而忽略了儒家“善”概念可能具有的超验性含义，恐有失妥当。譬如《大学》的“止于至善”与《孟子》 “圣而不可知之之谓神”所影射的“善”概念以及儒家“下学上达”、“天人合德”、“尽心知性以知天”等沟通道德之经验领域与超验领域的诸项命题，似乎都不是“人 与人之间适当关系”的经验范式所能穷尽的。因此，“善”除了具有经验性的实践义之外，似乎应该还有一种道德本体论的指涉。这一道德本体论指涉不仅为儒家道德哲 学的超验范畴提供依据，而且从根本上指向了儒家道德哲学生生不已的道统意识。 “Shan” (Moral Goodness) is one of the most important and central concepts in Confucian moral philosophy, and in many ways constitute the pivot to Mencius’s discussions about human nature. National Taiwan University professor Fu Pei-Jen once defined "Shan" as "the implementation of appropriate relations amongst peoples". The advantages of this definition are its all-encompassing inclusion of other Confucian cardinal values such as Ren, I, Li, Zhi, Siao and Ti, and the fact that it is strongly supported by various Confucian texts. However, such a definition solely restricts Confucian moral ideals to an experiential landscape, and ignores the possible transcendent connotations of the "Shan" concept. For example, Confucian precepts and sayings found across "The Greater Learning", "Mencius" and "Confucian Analects" which set out to engage and communicate both the experiential and transcendent fields of morality, are not adequately addressed by the experiential paradigm that Fu's definition inspires. Therefore, we believe that the "Shan" concept should not be limited to its undeniable practical connotations, but should also incorporate some form of ontological moral discussion. This ontological moral discussion not only forms the basis of which the transcendent category in Confucian moral philosophy is centered, but also points towards the interminable and regenerative state of moral consciousness in Confucian orthodoxy.